Analisis Trend Klaim Spm (Surat Pernyataan Miskin) Periode 2021-2023 di RSUD Genteng Kabupaten Banyuwangi - Roviqoh, Nur; Hasim, Maulidia; Fadila, Nur; Lestari, Putri Catur Ayu (Lembaga Yasin AlSys, 2025)
The Poor Statement Letter (SPM), or Certificate of Poverty, is an essential instrument for underprivileged communities in Banyuwangi Regency to access healthcare services. The increasing number of SPM claims at RSUD Genteng from 2021 to 2023 highlights challenges in budget management and claim administration. This study employs a descriptive quantitative design with a trend analysis approach to examine the patterns of increasing SPM claims at RSUD Genteng. Data were collected from monthly claim recapitulations at RSUD Genteng and interviews with finance department staff, then analyzed using descriptive statistics to visualize claim trends through line charts. The findings indicate that total SPM claims increased from IDR 5.48 billion in 2021 to IDR 10.6 billion in 2023, with the highest claim value recorded in September 2022 (IDR 647,152,400) and the lowest in February 2021 (IDR 153,169,200). Some claims from 2022 were settled only in 2023 due to the lengthy claim process at the central government level and turnover among claim officers. This study concludes that the increase in SPM claims reflects a high demand for healthcare services, while fluctuating patterns and delays in claim payments highlight the need for efficient and transparent claim management to maintain the financial stability of RSUD Genteng and ensure the sustainability of healthcare services for underprivileged communities.